2019
DOI: 10.1080/23808993.2019.1585805
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning and radiomics in precision medicine

Abstract: Introduction: The radiological reading room is undergoing a paradigm shift to a symbiosis of computer science and radiology using artificial intelligence integrated with machine and deep learning with radiomics to better define tissue characteristics. The goal is to use integrated deep learning and radiomics with radiological parameters to produce a personalized diagnosis for a patient. Areas covered: This review provides an overview of historical and current deep learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(128 citation statements)
references
References 73 publications
1
118
0
2
Order By: Relevance
“…In conclusion, we have demonstrated that mpRad framework shows excellent potential in analysis of textural information using multiparametric breast imaging data. These methods can be extended and used in different clinical applications beyond those presented in this work [50]. With increasing use of multiparametric imaging in clinical setting, mpRad provides an ideal framework for future clinical decision support systems.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have demonstrated that mpRad framework shows excellent potential in analysis of textural information using multiparametric breast imaging data. These methods can be extended and used in different clinical applications beyond those presented in this work [50]. With increasing use of multiparametric imaging in clinical setting, mpRad provides an ideal framework for future clinical decision support systems.…”
Section: Discussionmentioning
confidence: 99%
“…As in medical radiology, the possibilities and perspectives of the use of radiomics‐based and AI‐based analyses combined with the radiologist's analysis will revolutionize the DMFR, as shown in Figure .…”
Section: Augmented Dmfr: a New Perspectivementioning
confidence: 99%
“…DL is expected to leverage large-scale collections of images to extract clinical aspects not immediately and/or clearly associated to a clinical question. Despite being efficient, Dl is known to be not exempt from hurdles of various nature (8,9). Therefore, as medical images span informative details far beyond the possible answers to any specific clinical question, next generation computational inference tools (DL and other types) should be tuned to the assembling and processing of information while preserving interpretability of results.…”
Section: Precision Medicine Focusmentioning
confidence: 99%